Clinical study on basal blood perfusion in the major arteries of the limbs - Zhang, Rongji; Wang, Hao; Shi, Ji; Gao, Minghan; Li, Jianhui; Zhang, Jianzheng (Frontiers in Medicine, 2025)
BackgroundInvestigating basal blood perfusion in the major arteries of the limbs to guide flow rate selection during ex vivo perfusion preservation for limb replantation (transplantation).MethodsVolunteers undergoing physical examinations at PLAGH Fourth Medical Center (February–December 2024) were recruited. Three hundred and four eligible participants (146 males, 158 females; aged 18–65, mean 41.68 ± 11.28) were enrolled after screening. A portable Doppler ultrasound system was utilized to assess the brachial, ulnar, radial, popliteal, dorsalis pedis, and posterior tibial arteries in the limbs. Vascular diameter, blood flow velocity, and blood perfusion volume were measured for each artery. Mean hemodynamic parameters were calculated. Analyze the linear relationship between BMI, body surface area, and arterial blood perfusion volume using a multiple linear regression model. Conduct interaction tests to investigate whether there are sex-specific or “three-high” status-specific effects in the linear prediction model of blood perfusion volume by BMI and body surface area.ResultsUltrasound findings revealed the following mean blood perfusion volumes in the upper limb arteries: brachial artery, 74.9 ± 22.5 mL/min; ulnar artery, 35.7 ± 12.6 mL/min; radial artery, 36.8 ± 13.5 mL/min. In the lower limb arteries, the mean blood perfusion volume was: popliteal artery, 114.1 ± 34.2 mL/min; dorsalis pedis artery, 53.3 ± 18.1 mL/min; posterior tibial artery, 59.2 ± 21.0 mL/min. No significant difference was observed in mean blood perfusion volume between the ulnar and radial arteries (p > 0.05), whereas the posterior tibial artery exhibited significantly higher blood perfusion volume compared to the dorsalis pedis artery (p < 0.001). Multiple linear regression analysis revealed that BMI was negatively associated with arterial blood perfusion volume in the extremities, while body surface area showed a positive association. Furthermore, BMI and body surface area jointly formed a linear predictive relationship with limb blood flow. Based on significant effects within the linear model and pathophysiological mechanisms, interaction terms for body surface area (BSA) × BMI and age × diabetes status were included. The results demonstrated a statistically significant interaction effect (p < 0.05) between BMI and body surface area on limb blood flow. However, the interaction effect of diabetes status on limb blood flow was not significant (p > 0.05).ConclusionQuantitative ultrasound-derived limb perfusion parameters and their BMI/BSA correlations enable hemodynamic customization for machine perfusion systems in limb replantation. This standard approach balances metabolic support and ischemia-reperfusion risk mitigation during extracorporeal preservation, advancing personalized transplant protocols.